Smart Robotic Bin on Wheels - Dr. M. Ranga Rao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The robotic bin moves on its own to catch the object. Here we are placing the basket on robot to catch the object. A High efficient camera is attached to the robot which is used to track the object. In this we are using Intel Atom Processor for which camera is interfaced. This camera captures the object and the processor decides the path of object and moves the robot in that direction to catch the thrown object. For the movement of robot a wheel mechanism is used. This mechanism helps to move the robot in the direction of object and with the angle at which object lands. Hence the object directly catches by the robot into the basket. Since this project is done by Japanese and now we took the first step to implement this project. The advantages of this project are it is very useful for handicaps and if any valuable object is to be fallen suddenly this robot catcher will be very useful for it.